Analytical and Kinetic Behaviour of N-Bromoimide-mercuric Acetate System towards Aromatic Aldehydes: A Mechanistic Study - Anjum, Amena; Srinivas, P. (Asian Journal of Chemistry, 2010)
The oxidative kinetics of benzaldehydes, viz., 4-bromo, 4-chloro, 4-methyl, 3-nitro benzaldehydes has been carried out by N-bromophthalimide in presence of excess of mercuric acetate in aqueous acetic acid medium. Results of detailed kinetic effects, viz., solvent, temperature, concentration and salt effects, support the Michaelis. Menten type of mechanism. The stoichiometric ratio of N-bromophthalimide : benzaldehyde, was 1 : 1. The product of oxidation was benzoic acid, which was confirmed by HPLC and spot tests. Thermodynamic and activation parameters have been presented. Effect of substituents has been dealt with and order of reactivity established.